PERPUSTAKAAN DIGITAL UNTUK MENINGKATKAN LITERASI SISWA DI SDN KALISALAM 1 PROBOLINGGO - Sriwijayanti, Ribut Prastiwi; Hariyanto, Budi; Sari, Mala Sastia (Abdi Panca Marga, 2023)
The lack of optimal implementation of the literacy movement in reading corners and libraries has resulted in a lack of interest by teachers and students in reading. The formulation of the problem from this research is how to implement digital libraries to increase 21st-century student literacy in community service (KKN) at SDN Kalisalam 1 Probolinggo. In the digital library implementation project involving students and related to the development of digital libraries involving the school. This research is qualitative. This research data analysis uses descriptive analysis. In this research, data sources were obtained, namely primary data sources and secondary data sources. The techniques used in collecting data are literature study, interviews, observation, and documentation. The results of the research show that this digital library is very suitable to be the best alternative in facing the demands and challenges of literacy in the 21st Century Skills era. Implementation through digital literacy activities at SDN Kalisalam 1 Probolinggo, not only increases student and teacher literacy but also develops student character. Literacy activities such as reading books encourage students to obtain information that can shape the behavior and actions they internalize. This plays an important role in shaping student character. Keywords: 21stCentury Skills, Digital Library, Student Literacy.